Most appropriate conditions of the binding of LH in Benign and Malignant - Baghdad Science Journal (مجلة بغداد للعلوم)
Test method was developed radioimmunotherapy to appoint in two groups of patients infected with a uterine tumor Great conditions in tumor tissue benign and malignant Ddh teacher radioactive iodine isotope